The Burden of Pain Symptoms in Individuals with Uterine Fibroids–Results from a Prospective Observational Study in the USA - Hunsche E; Marshall NJ; See JZ; Rakov VG; Levy B (International Journal of Women's Health)
Elke Hunsche,1 Nell J Marshall,2 Jermyn Z See,2 Viatcheslav G Rakov,1 Barbara Levy3 1Sumitomo Pharma Switzerland GmbH, Basel, Switzerland; 2Evidation Health Inc, San Mateo, CA, USA; 3Department of Obstetrics and Gynecology, University of California, San Diego, San Diego, CA, USA; Department of Obstetrics and Gynecology, The George Washington University, Washington, DC, USACorrespondence: Elke Hunsche, Global Market Access and Health Economics / Outcomes Research, Sumitomo Pharma Switzerland GmbH, Aeschengraben 27, Basel, 4051, Switzerland, Tel +41 43 210 8129, Email elke.hunsche@ch.sumitomo-pharma.comPurpose: To characterize the burden of uterine fibroids (UF) in individuals experiencing heavy menstrual bleeding (HMB) and moderate-to-severe UF-associated pain in terms of symptoms experienced, impact on work and activities, and pain medication use both on menstrual and non-menstrual days.Patients and Methods: This prospective, real-world, observational study enrolled 350 participants in the USA with a self-reported UF diagnosis, HMB, and moderate-to-severe pain due to UF. Data collection took place from February 9 to July 19, 2021. Over 4 months, participants used an online platform to self-report daily menstrual status, bleeding intensity, UF-associated pain severity, and pain medication use, and to complete weekly work and productivity questionnaires. Results were analyzed descriptively and are reported for the overall population, by pain medication subgroups—defined based on the most potent medication taken—and menstrual versus non-menstrual days/weeks.Results: The analysis population consisted of 307 participants with ≤ 5 consecutive missing days of daily survey responses or ≥ 75% completion rate of the daily surveys. Mean age of participants (standard deviation; SD) was 37.2 (6.3) years. At baseline, 54.1% of participants reported not currently taking medication for treatment of HMB. Over the study period, mean UF-associated pain scores (SD; scale range 0– 10) were higher on menstrual days (3.5 [2.7]) than non-menstrual days (1.0 [1.8]), and this was consistent across medication use subgroups. Pain medications were used more frequently on menstrual days than non-menstrual days (22.9% versus 3.7% days of pain medication use, respectively). Participants reported 31.5% work impairment on menstrual weeks versus a 12.7% work impairment on non-menstrual weeks.Conclusion: In this study, UF-associated pain symptoms coincided with a reduction in individuals’ ability to take part in both work and non-work activities and an increase in pain medication use, particularly during menstrual weeks. These results highlight the need for improved diagnosis and pain management strategies in UF.Keywords: UF symptoms, heavy menstrual bleeding, pain medication, work productivity